Sodium-Glucose Cotransporter 2 Inhibitor Use Among Individuals Age <65 with Type 2 Diabetes and Heart Failure with Reduced Ejection Fraction: A Cost–Benefit Analysis - Glover S; Borrego ME; Ray GM; Roberts MH (Dove Medical Press, 2022)
Sarah Glover, Matthew E Borrego, Gretchen M Ray, Melissa H Roberts College of Pharmacy, University of New Mexico, Albuquerque, NM, USACorrespondence: Melissa H Roberts, College of Pharmacy, University of New Mexico, MSC09 5360, 1 University of New Mexico, Albuquerque, NM, 87131, USA, Tel +1 505-925-0953, Fax +1 505-272-6749, Email MHRoberts@salud.unm.eduBackground: Type 2 diabetes (T2D) patients face increased risk of heart failure (HF) as they age. Sodium-glucose cotransporter 2 inhibitors (SGLT-2i) have demonstrated effectiveness in reducing HF hospitalizations in patients with T2D and HF with reduced ejection fraction (HFrEF). Diabetes guidelines recommend SGLT-2i therapy for patients with HFrEF; however, SGLT-2i cost is high.Objective: Study objectives were to assess SGLT-2i utilization and HF hospitalization rates in commercially insured adults (age < 65) with T2D and heart failure with reduced ejection fraction (HFrEF) taking metformin with/without SGLT-2i use and conduct a cost-benefit analysis of SGLT-2i use from payer and societal perspectives.Methods: Economic models included HF hospitalization rates from real-world data (RWD) and hospitalization rate reductions from RWD and SGLT-2i clinical trials. Real-world HF hospitalization rates were obtained from claims data (MarketScan Commercial Database, years 2013- 2018). Societal perspective analyses included indirect costs. Sensitivity analyses were conducted on key parameters.Results: Among adults with T2D and HFrEF age 30- 64, SGLT-2i use increased (1.1% to 17.4%) between 2013 and 2018. The HF hospitalization rate without SGLT-2i use vs with was 15.5% vs 11.0% (absolute risk reduction of 4.5%). Base case scenario net-benefit was negative across all payer perspective models, while positive for societal-perspective. Payer perspective overall net-benefit in 30- 64 population: −$1,725,758 (−$4106 per person). Societal perspective net-benefit in 30- 64 population: $5,996,851 ($14,269 per person). In sensitivity analyses, estimated per person base case societal net-benefit of $14,269 was most sensitive to changes in baseline HF hospitalization rates, post-discharge mortality rates, and readmission rates. Lowering SGLT-2i prescription costs 50% and 80% resulted in per person net-benefit increases of $1737 and $4004, respectively.Conclusion: SGLT-2i utilization has steadily increased, with lower HF hospitalization rates observed among SGLT-2i users. Societal benefits of SGLT-2i use in this population are substantive; payer benefits are negative unless SGLT-2i cost is drastically reduced.Keywords: type 2 diabetes, heart failure, cardiovascular disease, economic impact, cost benefit, net benefit